A critical realist approach to systems thinking in evaluation. (January 2022) - De Souza, Denise E.
Pawson and Tilley's acknowledgment of programs embedded in multiple social systems has gained little traction in realist synthesis and evaluation practice. A practice focusing on fairly closed systems—explaining how programs work and do not work—has emerged. This article negotiates the boundaries of knowledge pertinent to have in program design and evaluation from a realist perspective. It highlights critical realism as another possible response to systems thinking in evaluation. Moving one level up a program, it theorizes about social structures, mechanisms, and causes operating in a complex system within which an education-to-work program is nested. Three implications of the approach are highlighted: it foregrounds the relational nature of social, psychological, and programmatic structures and mechanisms; enables policymakers to develop a broader understanding of structures needed to support a program; and enables program architects to ascertain how a planned program might assimilate and adapt to social structures and mechanisms already established in a context.